Geotechnical engineering for sustainable transportation infrastructure - Correia, A. Gomes (2015)
This paper highlights how transportation geotechnics can interact with transportation infrastructures and how through the planning, design, construction and maintenance can contribute to ensure solutions more safe, reliable and resilient in the future. In this context sustainable concepts are discussed and applied as best practices to preserve natural resources and assuring socio-economic and environment benefits for the society